Psychological Approaches to Enhancing the Effectiveness of Learning at Madrasah Tsanawiyah Pesantren Persis 88 in Cimahi City - Asep Sobirin; Tarsono (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to explore the role of psychological approaches in enhancing learning effectiveness at Madrasah Tsanawiyah (MTs) Pesantren Persatuan Islam (Persis) 88 in Cimahi City. The psychological approach utilized involves a comprehensive understanding of students' psychological needs, such as motivation, emotions, and interpersonal relationships, to support the teaching and learning process. This research employs a qualitative method with a case study approach. Data were collected through observations, interviews with teachers and students, and analysis of learning documents. The results show that the consistent application of psychological approaches can increase student engagement, improve interaction patterns between teachers and students, and foster a conducive learning atmosphere. Key factors supporting the success of this approach include teachers' competence in understanding students' psychological aspects, the use of adaptive teaching strategies, and a learning environment that accommodates students' emotional needs. These findings are expected to serve as a reference for other educational institutions in optimizing learning effectiveness through psychological approaches.